Diamondback Moth Larvae Trigger Host Plant Volatiles that Lure Its Adult Females for Oviposition - Hussain, Mubasher (Insects, 2020)
SIMPLE SUMMARY: The diamondback moth is a serious pest of crucifer crops. To control this pest, the use of intercropping (such as trap crops) is gaining attention since they are ecologically safe. However, such approaches require an understanding host plants which are most attractive to the pest. In this study, we quantified different volatiles released by Barbarea vulgaris in response to the diamondback moth larval feeding. We investigated olfactory responses of the adult diamondback moth to natural and simulated volatiles released by infested plants. We also investigated how volatile effects changed in response to larval feeding treatments. Overall, our findings indicated the relationship between key volatile compound, host plant cues emission and regulation of the diamondback moth adult female behavior due to key volatile triggered by the diamondback moth larvae feeding on B. vulgaris. ABSTRACT: The diamondback moth (DBM) is a destructive pest of crucifer crops. In this study, DBM larvae shown to herbivore induced plant volatiles (HIPVs) that were attractive to adult females exposed in a Y-tube olfactometer. Our results showed that olfactory responses of adult females to HIPVs induced by third instar larvae feeding on Barbarea vulgaris were significantly higher (20.40 ± 1.78; mean moths (%) ± SD) than those induced by first instar larvae (14.80 ± 1.86; mean moths (%) ± SD). Meanwhile, a significant concentration of Sulphur-containing isothiocyanate, 3-methylsulfinylpropyl isothiocyanate, and 4-methylsulfinyl-3-butenyl isothiocyanate were detected in HIPVs released by third instar larvae compared to those released by first instar larvae while feeding on B. vulgaris. When the DBM females were exposed to synthetic chemicals, singly and in blend form, a similar response was observed as to natural HIPVs. Our study demonstrated that the relationship between isothiocyanates acting as plant defense compounds, host plant cues emission and regulation of the DBM adult female behavior due to key volatile triggered by the DBM larvae feeding on B. vulgaris.